Network pharmacology-based prediction and “gut microbiota-inflammation-brain axis” validation of the active ingredients and potential mechanisms of Plantagins Herba for treating diabetes-related cognitive dysfunction - Huang, Zhixuan; Liu, Jian; Li, Hui; Ai, Yangwen; Zhou, Dongyue (Frontiers in Pharmacology, 2025)
BackgroundDiabetes-related cognitive dysfunction (DRCD) is increasingly recognized as a common complication. However, there are currently no specific remedies for DRCD. Plantagins Herba contains many active ingredients that can regulate blood lipids and blood glucose. It is used to treat cognitive impairment, but its therapeutic effects and molecular mechanisms on DRCD have not been reported.PurposeTo study the bioactive components, potential targets and molecular mechanisms of Plantagins Herba in the treatment of DRCD.MethodsNetwork pharmacology was applied to predict the active component of Plantagins Herba and the therapeutic targets of diabetes-related cognitive impairment. The molecular docking of the core components with the key targets was verified. Cell and animal models were established, and the mechanism by which hispidulin treats DRCD was explored via flow cytometry, Western blotting, behavioral experiments, HE staining, immunofluorescence, 16S rRNA and other techniques.ResultsBased on the network pharmacology analysis, hispidulin derived from Plantaginis Herba was identified as a promising candidate for further investigation. The computational predictions suggest that the MAPK and PI3K/AKT signaling pathways may play pivotal roles in DRCD pathogenesis. In vitro, Hispidulin reduced inflammation and apoptosis in BV2 cells. It also improved the viability of HT22 cells under inflammation conditions and increased the expression levels of β-catenin and Cyclin D1 proteins. In vivo, hispidulin significantly reduced glucose and lipid metabolism disorders and the abundance of harmful flora in diabetic mice with cognitive impairment. The immunofluorescence results suggested that hispidulin reduced the activation of microglia in the mouse brain and decreased inflammation. The expression of p38MAPK/PI3K/AKT signaling pathway and β-catenin, Cyclin D1 protein, which confirmed regulatory effect of Hispidulin in hippocampal tissue.ConclusionHispidulin ameliorated disease manifestations in a DRCD-induced murine model, attenuating neuroinflammation and histopathological damage in hippocampal tissues through gut microbiota modulation.